Lee Kuan Yew’s legacy : a Singaporean Singapore - Singh, Bilveer (2015)
While the physical transformation of Singapore from Third World to First is well-known, Mr. Lee Kuan Yew’s lasting achievement was building a Singaporean nation out of its diverse people.